CFD Modelling of Hydrodynamics and Heat Transfer in Channels of a PHE - Stogiannis, I. A.; Paras, S. V.; Arsenyeva, O. P.; Kapustenko, P. O. (The Italian Association of Chemical Engineering, 2013)
Plate Heat Exchangers (PHEs) are one of the most efficient types of contemporary heat exchangers with intensified heat transfer. They are commonly used in process industries due to their compactness, lower weight and cost, smaller space for installation and servicing compared to conventional shell-and-tube heat exchangers. Heat transfer in PHEs takes place in channels of complex geometry formed by corrugated plates placed abutting. The flow in such channels can be very complicated due to breakup and reattachment of the boundary layer, secondary flows and the small hydraulic diameter of the flow passages. The aim of this work is to compare a well-established and validated CFD code both with results obtained from an experimental PHE model using a corrugated plate commonly used in industrial applications and with existing correlations. The results show that CFD simulation can predict heat transfer rate and fluid flow behaviour in a range of Re numbers (8,900 to 27,650), with discrepancies up to 1 % and 6 % in terms of outlet temperature and pressure drop respectively. Modelling of the flow inside a single corrugation also allows for computation of the wall shear stress distribution which can be very useful in PHE applications where fouling is of particular importance.